Rhododendron cuneifolium - Tsen, S.; Mohd Yusof, Nur Adillah, M.Y.; Khoo, E.; Maryani, A.; Colin Ruzelion Maycock; Nilus, R.; Sugau, J.; Pereira, J.T. (International Union for Conservation of Nature and Natural Resources, 2021)
Rhododendron cuneifolium is a small tree, endemic to Sabah. The estimated area of occupancy (AOO) and extent of occurrence (EOO) are 120 km2 and 2,837 km2, respectively. It is known from at least four protected areas and currently does not have any major threat to its population. Hence, it is assessed as Least Concern. Rhododendron cuneifolium is endemic to Sabah, Malaysia.